2021
DOI: 10.1371/journal.pone.0248825
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene practices among high school girls in urban areas in Northeastern Ethiopia: A neglected issue in water, sanitation, and hygiene research

Abstract: Background Poor menstrual hygiene practices influence school girls’ dignity, well-being and health, school-absenteeism, academic performance, and school dropout in developing countries. Despite this, menstrual hygienic practices are not well understood and have not received proper attention by school WASH programs. Therefore, this study examined the extent of good menstrual hygiene practices and associated factors among high school girls in Dessie City, Amhara Region, northeastern Ethiopia. Methods A school-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 25 publications
(77 reference statements)
10
38
1
6
Order By: Relevance
“…Yohannes Habtegiorgis et al . [ 13 ] performed a study on menstrual hygiene practices among high-school girls in Northeastern Ethiopia in 2020 and have found that during multivariable analysis, maternal education, age, knowledge, and discussing menstrual hygiene with friends were significantly associated with good menstrual hygiene practices. Girls 16–19 years old were 1.9 times more likely to have good menstrual hygiene practices than girls in the 13–15-years age group (AOR = 1.93, 95% CI: 1.22–3.06).…”
Section: Discussionmentioning
confidence: 99%
“…Yohannes Habtegiorgis et al . [ 13 ] performed a study on menstrual hygiene practices among high-school girls in Northeastern Ethiopia in 2020 and have found that during multivariable analysis, maternal education, age, knowledge, and discussing menstrual hygiene with friends were significantly associated with good menstrual hygiene practices. Girls 16–19 years old were 1.9 times more likely to have good menstrual hygiene practices than girls in the 13–15-years age group (AOR = 1.93, 95% CI: 1.22–3.06).…”
Section: Discussionmentioning
confidence: 99%
“…Where the physical state of WASH infrastructure was mentioned, it related to the quantity of available and physically functional toilets/latrines [22,26,28,32,33,37,40,44,46,58,63,73,75,76,78,81,86,87,89,91], the design of toilets/latrines [32,37,40,44,48,51,57,63,64,68,71,73,75,81,83,87,90,97], the quality and availability of running water in and around toilets or latrines [18,20,31,33,37,39,40,45,46,48,49,…”
Section: Reasoning Behind Behaviourmentioning
confidence: 99%
“…availability of soap for washing [20,33,49,53,54,[56][57][58]60,61,63,64,66,67,73,77,90,91] and the availability of a physically functional disposal mechanism and/or service for used material [18,28,[31][32][33][34][35][36][37]42,[44][45][46][47][48]52,53,57,58,60,62,63,[66][67][68]71,76,77,82,83,86,90,91,…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations